Therapeutic Peer Play sebagai Upaya Menurunkan Kecemasan Anak Usia Sekolah selama Hospitalisasi - Solikhah, Umi (Jurusan Keperawatan FIKES UNSOED, 2011)
Anxiety is a reaction that often occurs in children during hospitalization and the resulting decline in condition, duration of adaptation, and developmental disorders. The writing is aimed to investigate the effect of therapeutic-peer-play against the anxiety of school-age children who were hospitalized, which is obtained from the research results. The study design using quasy-experiment, pre-test post-test control-group design, and each sample 33 in the intervention and control groups. Data analysis with paired t-test. Results showed there were significant effects (p-value = 0.000) against the anxiety of 11.09 3.73 in the intervention and control (66%); of anxiety is a mild anxiety. Given the therapeutic-peer-play affects the anxiety of school-age children who are treated, it is necessary to increase efforts to play the role of nurses towards therapeutic school-age children during hospitalization